Central T cell tolerance: Identification of tissue-restricted autoantigens in the thymus HLA-DR peptidome. (June 2015) - Alvarez, Iñaki; Collado, Javier A.; Colobran, Roger; Carrascal, Montserrat; Ciudad, M. Teresa; Canals, Françesc; James, Eddie A.; Kwok, William W.; Gärtner, Martina; Kyewski, Bruno; Pujol-Borrell, Ricardo; Jaraquemada, Dolores
Abstract: Promiscuous gene expression (pGE) of tissue-restricted self-antigens (TRA) in medullary thymic epithelial cells (mTECs) is in part driven by the Autoimmune Regulator gene ( AIRE ) and essential for self-tolerance. The link between AIRE functional mutations and multi-organ autoimmunity in human and mouse supports the role of pGE. Deep sequencing of the transcriptome revealed that mouse mTECs potentially transcribe an unprecedented range of >90% of all genes. Yet, it remains unclear to which extent these low-level transcripts are actually translated into proteins, processed and presented by thymic APCs to induce tolerance. To address this, we analyzed the HLA-DR-associated thymus peptidome. Within a large panel of peptides from abundant proteins, two TRA peptides were identified: prostate-specific semenogelin-1 (an autoantigen in autoimmune chronic prostatitis/chronic pelvic pain syndrome) and central nervous system-specific contactin-2 (an autoantigen in multiple sclerosis). Thymus expression of both genes was restricted to mTECs. SEMG1 expression was confined to mature HLA-DR hi mTECs of male and female donors and was AIRE-dependent, whereas CNTN2 was apparently AIRE-independent and was expressed by both populations of mTECs. Our findings establish a link between pGE, MHC-II peptide presentation and autoimmunity for bona fide human TRAs. Highlights: Peptides from tissue-restricted human autoantigens are presented by thymic HLA-DR. Semenogelin-1 and contactin-2 are target autoantigens in human autoinmune diseases. Genes encoding these antigens are exclusively expressed by mTECs in the thymus. Expression of these genes is differentially correlated with AIRE expression. These data link MHC-II presentation and autoimmunity with promiscuous gene expression.